2017
DOI: 10.4172/2380-2391.1000224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Particulate Matter-Based Air Quality Index in Port Harcourt, Nigeria

Abstract: Due to the desire of nations to enhance their economic status, industrialization is vigorously pursued. Industrialization is historically associated with environmental degradation. In developing countries, due to lack of environmental awareness, the level of industrialization is not commensurate with environmental studies and monitoring. This study was designed to assess the status of particulate matter at three emerging industrial sites in Port Harcourt. To achieve this, Aerocet 531 monitor was used. To be ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
29
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 6 publications
5
29
3
Order By: Relevance
“…The presence of daily PM 2.5 at 32-158 µg/m 3 and PM10 at 33-467 µg/m3 beyond WHO acceptable limits, con rms the likelihood of Port Harcourt residents being exposed to hazardous compounds [60,61]. High amounts of ne particulate matter in indoor and outdoor environs noted in the study were similar to those found in highly petroleum-based industrial areas [23][24][25][26][27][62][63][64]. The observed increase in particulate matter is most likely responsible for the relative upsurge in trends of morbidity and mortality recorded over the years in Port Harcourt, con rming reports from previous studies [19,20,62], as toxicity and mortality, cancers, upsurge in respiratory, cardiovascular, and renal dysfunctions resulting from exposure to particulate matter bonded with PAHs have been reported in a plethora of epidemiological studies [47,65,44].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…The presence of daily PM 2.5 at 32-158 µg/m 3 and PM10 at 33-467 µg/m3 beyond WHO acceptable limits, con rms the likelihood of Port Harcourt residents being exposed to hazardous compounds [60,61]. High amounts of ne particulate matter in indoor and outdoor environs noted in the study were similar to those found in highly petroleum-based industrial areas [23][24][25][26][27][62][63][64]. The observed increase in particulate matter is most likely responsible for the relative upsurge in trends of morbidity and mortality recorded over the years in Port Harcourt, con rming reports from previous studies [19,20,62], as toxicity and mortality, cancers, upsurge in respiratory, cardiovascular, and renal dysfunctions resulting from exposure to particulate matter bonded with PAHs have been reported in a plethora of epidemiological studies [47,65,44].…”
Section: Discussionsupporting
confidence: 64%
“…Unlike places such as Abuja where relative clean air have been noted [21,22], the ambient air quality of the crude oil-rich city of Port Harcourt has been reported to be polluted with particulate matter of petroleum origin, especially PM 10 (averaged 494 µg/m3) and PM 2.5 (averaged 155 µg/m3), and its constituent compounds including PAHs [23][24][25][26]. Using secondary data from hospital records, a signi cant increase in trends of respiratory morbidity, and mortality in Port Harcourt over the years, have been documented [20,23]. While Particulate matter containing PAHs results from incomplete combustion of hydrocarbons, inhabitants are exposed to PAHs through air inhalation and re-suspended soil and dust, consumption of food and water, and dermal contact with soil and dust [10,17,27].…”
mentioning
confidence: 99%
See 3 more Smart Citations